2005
DOI: 10.1086/432614
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of a Massive SCUBA Core with both Inflow and Outflow Motions

Abstract: We report the discovery of a massive SCUBA core with evidence of inflow and outflow motions. This core is detected by SCUBA at both 450 and 850 µm. Barely resolved by the telescope beam at 450 µm, it has a size of 10 ′′ , corresponding to 0.28 pc at a distance of 5.7 kpc. The dust temperature is estimated to be ≤ 29 K, the total mass is 820 M ⊙ and the average density is 1.1×10 6 cm −3 in a region with a radius of 5 ′′ . Follow-up spectral line observations, including HCN (3−2), HCO + (3−2), H 13 CO + (3−2) an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 22 publications
3
57
1
1
Order By: Relevance
“…As a consequence of the selection criteria, MSX data (Egan et al 2003) are available for all of the 51 sources of the sample. We found IRAS data (Helou & Walker 1988) for 45 sources, Scuba data for 12 sources at 450 μm and for 16 at 850 μm (Williams et al 2004;Wu et al 2005;Thompson et al 2006), and Calthech Submillimeter Observatory (CSO) data for 4 sources at 350 μm (Hunter et al 2000;Motte et al 2003). For 8 sources, we found measurements at 1.2 mm carried out with the IRAM 30 m Radiotelescope (Altenhoff et al 1994;Beuther et al 2002) and SIMBA (Faúndez et al 2004).…”
Section: The Dust Contributionmentioning
confidence: 89%
“…As a consequence of the selection criteria, MSX data (Egan et al 2003) are available for all of the 51 sources of the sample. We found IRAS data (Helou & Walker 1988) for 45 sources, Scuba data for 12 sources at 450 μm and for 16 at 850 μm (Williams et al 2004;Wu et al 2005;Thompson et al 2006), and Calthech Submillimeter Observatory (CSO) data for 4 sources at 350 μm (Hunter et al 2000;Motte et al 2003). For 8 sources, we found measurements at 1.2 mm carried out with the IRAM 30 m Radiotelescope (Altenhoff et al 1994;Beuther et al 2002) and SIMBA (Faúndez et al 2004).…”
Section: The Dust Contributionmentioning
confidence: 89%
“…The dense core JCMT 18354−0649S was first detected in an ammonia survey of high-mass star-forming regions with the Max-Planck-Institut für Radioastronomie (MPIfR) 100 m telescope at Effelsberg (Wu et al 2006), and was later confirmed by the observation with the Submillimeter Common-User Bolometric Array (SCUBA) of the James Clerk Maxwell telescope (JCMT; Wu et al 2005). Another SCUBA core which harbors a UC H ii region, G35.4 NW, is located about 1 north of JCMT 18354−0649S.…”
Section: Introductionmentioning
confidence: 94%
“…Another SCUBA core which harbors a UC H ii region, G35.4 NW, is located about 1 north of JCMT 18354−0649S. The kinetic distance of the two SCUBA cores is 5.7 or 9.6 kpc (Wu et al 2005), and 5.7 kpc was adopted in this paper. Core JCMT 18354−0649S has no counterpart in the radio continuum.…”
Section: Introductionmentioning
confidence: 99%
“…(EGOs, Chen et al 2010), which are shocked regions, and -0.5 for the cluster-forming clump G24.4 (Wu et al 2005).…”
Section: The Skewness Parameter δVmentioning
confidence: 99%